THE IMAGE OF PRESIDENT CANDIDATE JOKO WIDODO IN CAMPAIGN ADVERTISEMENT IN THE PRESIDENT ELECTION 2019 - Ridwan, Muhammad Fauzi; Priyatna, Aquarini; Meilinawati, Lina (Capture : Jurnal Seni Media Rekam, 2020)
This research focuses on Joko Widodo's and KH Maruf Amin's campaign in the 2019 presidential election. The purpose of this study is to find out how Joko Widodo imaged himself in his political campaign adverts, and how ideas and meanings are articulated in political advertisements. The study uses a descriptive qualitative research with Roland Barthes's Semiotic analysis approach. The results showed that Joko Widodo was represented as a simple leader, populist, and close to a low society, and could bring Indonesia forward and prosper through some of his programs are Kartu Prakerja or the Pre-Employment Card, Kartu Indonesia Pintar Kuliah or Indonesia Smart College Card, and Kartu Sembako Murah or Cheap Basic Food Cards.